Enhanced methanol oxidation on PtNi nanoparticles supported on silane-modified reduced graphene oxide. (1st February 2022) - Chen, Yizhe; Ma, Yanyun; Zhou, Yuqiao; Huang, Yufu; Li, Shumin; Chen, Yan; Wang, Ranran; Tang, Junping; Wu, Peng; Zhao, Xueling; Chen, Cheng; Zhu, Zhigang; et al.
Abstract: Developing low cost, highly efficient, and long-term stability electrocatalysts are critical for direct oxidation methanol fuel cell. Despite huge efforts, designing low-cost electrocatalysts with high activity and long-term durability remains a significant technical challenge. Here, we prepared a new kind of platinum-nickel catalyst supported on silane-modified graphene oxide (NH2 -rGO) by a two-step method at room temperature. Powder X-ray diffraction, UV–vis spectroscopy, Raman, FTIR spectroscopy and X-ray photoelectron spectroscopy results confirm that GO was successfully modified with 3-aminopropyltriethoxysilane (APTES), which helps to uniformly disperse PtNi nanoparticles. Cyclic voltammetry, chronoamperometry, CO-stripping and rotating disk electrode (RDE) results imply that PtNi/NH2 -rGO catalyst has significantly higher catalytic activity, enhance the CO toxicity resistance, higher stability and much faster kinetics of methanol oxidation than commercial Pt/C under alkaline conditions. Graphical abstract: Image 1 Highlights: Silane-modified graphene oxide (NH2 -rGO) is synthesized. PtNi nanoparticles are highly dispersed on NH2 -rGO support. Pt8 Ni2 /NH2 -rGO exhibited superior activity towards methanol oxidation. Pt8 Ni2 /NH2 -rGO had better CO poisoning tolerance and much faster kinetics of methanol oxidation.